Optimization and Verification of Gear Pump Cover Based On ANSYS and MATLAB - Jing, Shuangxi; Luo, Zhipeng; Luo, Chenxu; Yuan, Jinle; Yang, Xiaoyu (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: In the traditional design, parameters of the gear pump cover are based on the minimum thickness and gear shaft parameters, with shortcoming of wasting material and designing roughly. It is necessary to verify the advanced nature of improvement by the contrast in the changes of dynamic characteristics and the fatigue life of before and after changes gear pump cover optimization. Methods: the dynamic characteristics is analyzed by ANSYS. Different kinds of hydraulic loads, which influence the life of gear pump cover, are set to change with instantaneous flow or the form of ANSYS provided various variations. The time-amplitude curves are obtained in MATLAB. Frequencyamplitude curve of different hydraulic loads are obtained by FFT algorithm in MATLAB. The fatigue life of gear pump cover are analyzed by ANSYS. Results: By the simulation of ANSYS, the maximum equivalent stress of gear pump cover is reduced by 67%, and the first order of total displacement response is decreased by 42%. Under the hydraulic shock, which changes with the instantaneous flow, the fatigue life of pump cover is improved by 1491 times after the optimization. When the impact of oil is superimposed by the multi-frequency impact, it will result in the fatigue damage of gear pump cover which is more serious. Conclusion: The dynamic characteristics and the fatigue life of gear pump cover are improved significantly after being optimized. The effects on the life of the pump cover after optimization of different kinds of oil pressures changed with the forms of different loads, are improved significantly in different degrees. The study of oil pressure impact on the life of the pump cover indicates that the pump cover fatigue life is significantly reduced when the oil pressure changes drastically. In the design of the gear pump, the hydraulic shock on gear pump cover, which is changed by the instantaneous flow, should be taken into account.
Keywords: Gear pump cover